⁵¹V, ¹³C and ¹H FT-NMR Studies on Vanadium (V) Species in Aqueous Solutions - Habayeb, Adam H. Mahmoud (My University, 1981)
The solution chemistry of the Stretford Process - a liquid redox, cyclic process employed to efficiently remove hydrogen sulfide from sour gases - is not fully understood. The intent of the present work is to investigate the speciation of metavanadate ions in aqueous and in Stretford-like solutions; the interactions between vanadium (V) species and several oxygen- and nitrogen-donating ligands and the molecular microdynamics of several vanadium (V) species in aqueous solutions by means of multinuclear FT-NMR spectroscopies.
This thesis is comprised of three parts. In the first part, ⁵¹V FT-NMR chemical shifts, line widths, and area ratios obtained for various vanadium (V) species in aqueous solutions as functions of counter-ion, pH, and analytical vanadium concentration changes are reported. ⁵¹V chemical shifts are assigned to each of the following vanadium (V) species: VO₄³⁻, VO₂(OH)₂(H₂O)⁻, V₂O₇⁴⁻, HV₂O₇³⁻, V₃O₉³⁻, V₄O₁₂⁴⁻, V₆O₁₇⁴⁻, HnV₁₀O₂₈(⁶⁻ⁿ)⁻ and VO₂(H₂O)₄⁺. In the pH range 8.5 to 7.0, ⁵¹V FT-NMR resonances are observed at -574 ppm and -582 ppm. The resonance at -574 ppm is assigned to both the V₃O₉³⁻ and the V₄O₁₂⁴⁻ species, while the resonance at -582 ppm is assigned to the V₆O₁₇⁴⁻ species. The suggestion that tetralkyl ammonium cations stabilize V₃O₉³⁻ and/or V₄O₁₂⁴⁻ species in solution is confirmed.
In the second part, ⁵¹V FT-NMR chemical shifts and line widths obtained for the complexation of the pervanadyl cation [VO₂(H₂O)₄]⁺ with a series of dicarboxylic acids, α-and/or β-hydroxy carboxylic acids and polyaminocarboxylates are reported. Tentative structures for the observed complexes are proposed. Variations of δ⁵¹V with pH are noted. An attempt to explain the obtained δ⁵¹V in terms of the size and type of the ring formed is made. To help elucidate the structures of the complexes formed in solution, ¹³C and ¹H FT-NMR data are also reported.
The third part is comprised of two sections. In the first, spin-lattice relaxation times (ᴛ₁) are measured using the inversion recovery method for several vanadium (V) species present in solution in the pH range 14 to 1.0. At pH = 14, VO₄³⁻ is the only species present; ⁵¹V ᴛ₁ value for this species is 340 msec, while at pH 1.0 - where only VO₂(H₂O)₄⁺ is present - ᴛ₁ equals 0.7 msec. In the pH range 12-5, ᴛ₁ values are invariant with pH and are equal to 9 ∓ 1 msec. A structure that is consistent with the observed ⁵¹V ᴛ₁ value for the protonated form of VO₄³⁻ is proposed.
The second section discusses the temperature dependence of ⁵¹V spin-lattice relaxation times for the VO₄³⁻ species at pH 14. The results are consistent with the proposal that two relaxation mechanisms with opposite temperature dependencies are observed. A quadrupole relaxation mechanism predominates at temperatures below 310 K whereas a spin-rotation mechanim becomes more important at temperatures above 310 K.
Keywords: Chemistry; Chemistry